2016
DOI: 10.1002/jbm.a.35791
|View full text |Cite
|
Sign up to set email alerts
|

Roughness gradients on zirconia for rapid screening of cell‐surface interactions: Fabrication, characterization and application

Abstract: Roughness is one of the key parameters for successful osseointegration of dental implants. The understanding of how roughness affects cell response is thus crucial to improve implant performance. Surface gradients, which allow rapid and systematic investigations of cell-surface interactions, have the potential to facilitate this task. In this study, a novel method aiming to produce roughness gradients at the surface of zirconia using hydrofluoric acid etching was implemented. The topography was exhaustively ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…ResNet: ResNet was introduced to solve the unexpected low performance of deeper network architectures. The network uses skip connection to convey information from the previous input layer to the output layer [35]. Several variants with different output sizes exist, including Resnet-18, ResNet-34, ResNet-50, ResNet-101, and ResNet-152.…”
Section: Network Pre-trainingmentioning
confidence: 99%
“…ResNet: ResNet was introduced to solve the unexpected low performance of deeper network architectures. The network uses skip connection to convey information from the previous input layer to the output layer [35]. Several variants with different output sizes exist, including Resnet-18, ResNet-34, ResNet-50, ResNet-101, and ResNet-152.…”
Section: Network Pre-trainingmentioning
confidence: 99%
“…Previous studies have shown that a roughened zirconia surface will result in improved in vitro results compared to a machined or polished zirconia surface; therefore, the rationale of this investigation was to evaluate the osseointegration potential of a novel zirconia surface compared to a titanium surface [ 6 , 28 , 32 , 56 , 58 , 67 ]. In this study, micro- and nano-topographies were created on Y-TZP and CpTi surfaces by sandblasting and evaluated by laser scanning microscopy and SEM.…”
Section: Discussionmentioning
confidence: 99%
“…The micro- and nano-structure of implant surfaces is a significant factor for titanium and zirconia to achieve successful and reliable osseointegration [ 5 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Hence, various surface modifications have been used to modulate the physical and chemical properties aiming to improve bone-to-implant interaction [ 5 , 17 , 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying reason may be that the roughness gradient can induce significant changes in the cell area, aspect ratio, and solidity. Nano-roughness parameters were reported to be correlated with cell solidity linearly, while micro-roughness parameters appeared to correlate to cell area nonlinearly, highlighting the importance of multiscale optimization of implant surface roughness and topography to induce the desired cell response 36) . It has been demonstrated that microgrooves created on rough zirconia surface could modify the morphology and guide the size and alignment of human fetal osteoblasts.…”
Section: Surface Roughnessmentioning
confidence: 99%